Effect of Plant Growth Regulators on Soluble Carbohydrates, Photosynthetic Pigments and Chlorophyll Fluorescence of Sirvan and Homa Wheat Cultivars in Rainfed and Irrigation Conditions - F. sadeghi; Y. Sohrabi; A. Sio-Se Mardeh (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2022)
Adverse environmental conditions cause stress in plants, and some plant growth regulators (PGR’s) improve plant tolerance to these undesirable conditions. In order to study the effect of gibberellin, cytokinin and cycocle on some physiological traits of two wheat cultivars under different irrigation regimes, a study was conducted as a split-split plot experiment based on a randomized complete block design with three replications at the Agricultural Research Station of Kurdistan University, Sanandaj, Iran in 2016. Irrigation at four levels: rainfed, irrigation at booting stage, irrigation at booting + flowering and irrigation at booting + flowering + grain filling stages as the main plots, two wheat cultivars (Sirvan and Homa) as sub-plots and levels of plant growth regulators foliar application including control (no-PGR), gibberellin (100 µm), cytokinin (100 µm) and cycocel (3 g l-1) at the wheat stem elongation and grain filling stages as the sub-sub plots were examined. The results showed that soluble carbohydrates concentration was higher in rainfed conditions, compared to the other levels of irrigation. Relative water content, rate of water loss and maximum quantum yield of photosystem II (Fv/Fm) increased due to irrigation, relative to the rainfed condition. A higher chlorophyll a and total chlorophyll concentration was observed with cytokinin spray in the presence of the three irrigation treatments. The results also indicate that, at the stem elongation and grain filling stages, foliar application of gibberellin reduced the rate of leaf water loss. Application of cytokinin and cycocel increased the concent of carotenoids, application of gibberellin and cycocel increased the Fv/Fm and the use of all three PGR’s increased soluble carbohydrates concentration compared to the no-PGR condition. The highest grain yield was obtained with cytokinin and cycocel spray at the wheat stem elongation and with the application of cycocel at grain filling stages under the condition of irrigation at booting + flowering + grain filling stages. Homa cultivar produced a higher grain yield compared to Sirvan. It may be concluded that the application of cytokinin and cycocel is beneficial to some physiological attributes and hence increasing the grain yield of wheat.